Do Audit Committees Strengthen Reporting Quality? Evidence on Profitability, CSR, Liquidity, and Earnings Quality in IDX Firms (2019–2022) - Muhammad Rafi Fachruddin; Ardianto Ardianto (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates how earnings quality (EARNQUAL) is influenced by liquidity, corporate social responsibility (CSR), and profitability, with the audit committee (AC)considered as a moderating factor. This research employs a quantitative design and utilizes secondary data from the Indonesia Stock Exchange (IDX), ESGI database, and public company reports. During the 2019–2022 period, the sample observed 140 companies from industrial and basic materials companies listed on the IDX. Data analysis was performed using SPSS 26.0. This research is based on agency, stakeholder, and legitimacy theories. Despite extensive prior research on earnings quality determinants, empirical evidence on the moderating effectiveness of audit committees in emerging market settings remains inconclusive. The empirical results demonstrate that profitability exerts a positive and statistically significant impact on earnings quality. Conversely, CSR is not found to be significantly associated with earnings quality, while liquidity exhibits a negative effect. Furthermore, the moderation test indicates that the audit committee does not enhance the effects of profitability, CSR, or liquidity on earnings quality. This study contributes to the accounting literature by clarifying the limited governance role of audit committees in enhancing earnings quality when governance structures are homogeneous. The findings imply that strengthening earnings quality in Indonesian firms requires not only formal governance mechanisms but also improvements in the substantive effectiveness of audit committee oversight